PENGEMBANGAN PEMBELAJARAN VIRTUAL BERBASIS LMS SCHOOLOGY UNTUK MENINGKATKAN PRESTASI BELAJAR SISWA ( Studi Pengembangan Pada Mata Pelajaran Ekonomi Kelas XI IPS Di SMA Negeri 1 Pagar Alam) - Nurmala Sari; Johanes Sapri (DIADIK, 2021)
The aim of this study is to describe the development of a feasible LMS schoology-based virtual learning in improving the learning achievement of students in class XI IPS at SMA Negeri 1 Pagar Alam and to describe the effectiveness of developing a virtual learning based on LMS Schoology in improving student learning achievement at economy class XI IPS subject in SMA Negeri 1 Pagar Alam. In this study, a research and development design was used. Research subjects were students of class XI IPS at SMA Negeri 1 Pagar Alam. Data collection techniques used in the study were assessment sheets and student test results. Data analysis used mean and t-test. the material and media expert validation instrument in research was Likert. The conclusions of this study are The virtual learning based on LMS schoology developed is feasible to improve student learning achievement in economic learning and development of a virtual learning based on LMS Schoology is effective in improving student achievement based on the results of limited scale trials and the area of class XI IPS SMA Negeri 1 Pagar Alam in economic subjects